Urgensi Metode Pembiasaan Pendidikan Agama Islam Pada Anak Usia Dini Di Era Globalisasi - Yanti Amalia Afifah; Kinanti Siti Mufarihah2\; Salwa Khotimah; Sabariyah; Ane Zunnatul Mafruhah (TA'DIB: Jurnal Pendidikan Agama Islam, 2023)
Islamic religious education at an early age has a great influence on their lives in the future and to make it easier to develop it requires methods that are easy to apply, one of which is the habituation method. This study is aimed to analyze the importance of habituation method of Islamic education in early childhood. This research uses qualitative approach with analytical methods. The results of this research showed that applied RA Miftahul Huda Al-Mas’udiyah to teach PAI lessons to learners using habituation methods. Habituation methods are employed so that children can become accustomed to actualizing religious teachings in daily life, so that when a child grows up with religious knowledge and knowing of obligations as a Muslim.